Peripartum cardiomyopathy—An unsolved mystery to an anesthesiologist - Rashmi HD.; Prajwal Patel HS.; Shivaramu BT. (Universiti Kebangsaan Malaysia, 2015)
Cardiac diseases in pregnancy pose a multitude of challenges to both anesthesiologists and obstetricians. Peripartum cardiomyopathy is one of the rare causes of dilated cardiomyopathy in parturients with a great diagnostic difficulty. High degree of suspicion along with good clinical experience is needed for its diagnosis. Unfortunately, mortality from this ranges from 35% to 50%. We report a case of 21-year-old female parturient presenting at 37 weeks of gestation for emergency cesarean delivery with undiagnosed peripartum cardiomyopathy. She developed cardiac arrest soon after giving spinal anesthesia. She was successfully resuscitated and shifted to ICU for further management. Bedside echocardiography was conducted, which showed dilated cardiomyopathy with an ejection fraction of 32%.